Rancang Bangun Aplikasi Pelaksanaan Ujian dengan Menggunakan Metode Couple Linear Congruential Generator (CLCG) pada MTs Alfaizin Percut Sei Tuan Berbasis Android - Saragih, Vieri Irdiansyah; Mas Ayoe Elhias Nst (Universitas Methodist Indonesia, 2025)
At MTs Alfaizin Percut Sei Tuan, the conventional exam process presents several challenges, such as excessive paper usage, increased risk of cheating, and lengthy correction times. This study aims to develop an Android-based exam application using the Couple Linear Congruential Generator (CLCG) method. This method generates pseudo-random numbers that randomize exam questions, allowing each participant to receive a different set of questions, ultimately minimizing cheating. The application was developed using a waterfall model approach in the software development process. Test results show that the application runs well on Android devices, making it easier for teachers to administer exams and speeding up the assessment process. This application can be an effective solution to support the digitalization of the exam system in schools.